The effect of temperature changes on in vitro slow wave activity in the equine ileum. (4th March 2015) - Fintl, C.; Hudson, N. P. H.; Handel, I.; Pearson, G. T.
Summary: Reasons for performing study: Slow waves are rhythmic pacemaker currents generated by the gastrointestinal pacemaker cells, the interstitial cells of Cajal, and represent the rate‐limiting step for small intestinal smooth muscle contractions. Therefore, factors that affect slow wave activity may also influence contractile activity. It is not known how temperature changes may influence slow wave activity in the horse. This could be of relevance during colic surgery if cooling of exposed intestine resulted in reduced slow wave activity potentially exacerbating post operative ileus. Objectives: To evaluate the effect of temperature changes on in vitro slow wave activity of normal equine ileum using intracellular recording techniques. Study design: In vitro experimental study. Methods: A segment of ileum was collected immediately following euthanasia from 9 horses for reasons unrelated to the gastrointestinal tract. Intracellular recordings of membrane potentials were made from individual smooth muscle cells. The temperature of the tissue bath was altered during the course of each experiment across a range of 27–41°C. All data were recorded and stored using a computer‐interfaced acquisition system. A software package was used to analyse slow wave frequency, duration, amplitude and resting membrane potential. Results: In all 9 horses, slow wave frequency was highly temperature sensitive and approximately linearly related to the temperature over the range studied, increasing by 0.5 cycles/min for each 1°C increase in temperature (P<0.001). The initial slow wave frequency resumed when the temperature was returned to 37°C. The recovery time appeared to be directly related to the duration for which the temperature had been changed. Conclusions: Slow wave frequency in the equine ileum is highly temperature sensitive. As post operative ileus is a major cause of morbidity and mortality in the horse, the negative effect of lower temperatures on slow waves, and therefore contractile activity, should be considered.